Official publication of the Commonwealth Heads of Government Meeting 2002- (FIRST LondonGB, 2002)
Presents the addresses & papers emanating from CHOGM.
Documentation Centre has: 2002 (Coolum : 2- 5 March); 2009 (POS, 27-29 November); 2011 (Perth, 28 - 30 October)